Future Development Through the Past: Pathology of the Financing Dimension of Iran’s Health Transformation Plan - Doshmangir L; Najafi B; Mostafavi H; Moshiri E (Dove Medical Press, 2020)
Leila Doshmangir,1– 3 Behzad Najafi,1 Hakimeh Mostafavi,4 Esmaeil Moshiri5 1Tabriz Health Services Management Research Center, Iranian Center of Excellence in Health Management, School of Management and Medical Informatics, Tabriz University of Medical Sciences, Tabriz, Iran; 2Social Determinants of Health Research Canter, Health Management and Safety Promotion Research Institute, Tabriz University of Medical Sciences, Tabriz, Iran; 3Department of Health Policy and Management, School of Management and Medical Informatics, Tabriz University of Medical Sciences, Tabriz, Iran; 4Health Economy, Standard and Health Technology Office, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 5Social Determinants of Health Research Center, Semnan University of Medical Sciences, Semnan, IranCorrespondence: Leila Doshmangir Email Doshmangirl@tbzmed.ac.irBackground: In Iran, during the years, the budgeting model used for healthcare funding is affected by factors such as global oil prices and fluctuation in the exchange rates. So, developing or continuing to implement a plan in the health system depends on the current and future global and local economic trends.Objective: To analyze the future of the recent significant reform called Health Transformation Plan (HTP), started on June 15, 2014, in the light of potential financial barriers and challenges.Methods: Face-to-face interviews were conducted with health policymakers at different levels of the health system, health researchers, health insurance officers, and faculty members. Also, published and unpublished documents about HTP in the country and worldwide were reviewed. Data analysis was done using a qualitative inductive content analysis approach and assisted by qualitative data management software.Results: Instability of financial resources and allocation of gross domestic product (GDP) to the HTP in the traditional way is a challenge in continuing this policy reform. Also, the bureaucratic procedures in allocation and distribution of funds, the discrepancy between health insurance funds and affiliated units of Ministry of Health and Medical Education (MoHME) especially Medical Sciences Universities (MSU), the lack of purchaser–provider split, inappropriate payments and compensation mechanisms, and dependence of MSU on especial revenues are the main challenges that threaten the future of HTP in Iran.Conclusion: Given the current situation, where the country’s funding resources are often unpredictable, it seems that such funding challenges will lead to poor HTP results. Therefore, the continuance of such a high cost-based plan requires the strategies and policies to ensure raising additional funds through various types of innovative financing to overcome challenges.Keywords: Health Transformation Plan, health system, health policy, financing